Pengaruh Kepemimpinan, Komunikasi, Motivasi terhadap Kinerja: Influence of Leadership, Communication, and Motivation on Performance - Tri Listiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2018)
The method employed in this research are survey descriptive and survey explanatory, thatmeasured the relation and effect among research variables dan study the hypotesis whichhave been formulated first. Data analysis used path analysis, and the model of this pathdiagram shall always use a double headed arrow to denote a correlation, indicating thesymmetrical nature of a correlation. In tracing the paths of a diagram, a double-headedcurve may be used in either direction (from leadership to communication, or fromcommunication to leadership). Leadership and communication contributes to the thedetermination of work motivation, and work motivation gives to the determination ofemployee’s performance.Research findings shows that the total effect of leadership, communication and workmotivation on employees’ performance accounts for 0,563, and statistically significant. Thedirect effect of other variable on employees’ peformance account for 0,437, the result0,437says that the effect of other variabel on employees’ performance is moderate. Thesevariable was not investigated in this research, but theoretecally influenced employees’performance, that is ability of leader to achieve superior performance. The effect ofleadership to motivation account for 0,442, and the influence of communication tomotivation account for 0,517. Both of path coefficient from leadership and communicationto motivation statistically significant.Beside leadership and communication whichinfluenced motivation the others variable that affected motivation are the employeesinvolving in decision making process,and job satisfaction. These variable account for0,483, the result 0,483 says that thr effect on motivation is moderate.The leadership andcommunication corelation statistically significant